Effects of Carbocysteine and Beclomethasone on Histone Acetylation/Deacetylation Processes in Cigarette Smoke Exposed Bronchial Epithelial Cells. Issue 10 (31st March 2017) - Pace, Elisabetta; Di Vincenzo, Serena; Ferraro, Maria; Siena, Liboria; Chiappara, Giuseppina; Dino, Paola; Vitulo, Patrizio; Bertani, Alessandro; Saibene, Federico; Lanata, Luigi; Gjomarkaj, Mark
Abstract : Histone deacetylase expression/activity may control inflammation, cell senescence, and responses to corticosteroids. Cigarette smoke exposure, increasing oxidative stress, may negatively affect deacetylase expression/activity. The effects of cigarette smoke extracts (CSE), carbocysteine, and beclomethasone dipropionate on chromatin remodeling processes in human bronchial epithelial cells are largely unknown. The present study was aimed to assess the effects of cigarette smoke, carbocysteine, and beclomethasone dipropionate on histone deacetylase 3 (HDAC3) expression/activity, N‐CoR (nuclear receptor corepressor) expression, histone acetyltransferases (HAT) (p300/CBP) expression, p‐CREB and IL‐1 m‐RNA expression, neutrophil chemotaxis. Increased p‐CREB expression was observed in the bronchial epithelium of smokers. CSE increased p‐CREB expression and decreased HDAC3 expression and activity and N‐CoR m‐RNA and protein expression. At the same time, CSE increased the expression of the HAT, p300/CBP. All these events increased acetylation processes within the cells and were associated to increased IL‐1 m‐RNA expression and neutrophil chemotaxis. The incubation of CSE exposed cells with carbocysteine and beclomethasone counteracted the effects of cigarette smoke on HDAC3 and N‐CoR but not on p300/CBP. The increased deacetylation processes due to carbocysteine and beclomethasone dipropionate incubation is associated to reduced p‐CREB, IL‐1 m‐RNA expression, neutrophil chemotaxis. These findings suggest a new role of combination therapy with carbocysteine and beclomethasone dipropionate in restoring deacetylation processes compromised by cigarette smoke exposure. J. Cell. Physiol. 232: 2851–2859, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Cigarette smoke exposure, increasing oxidative stress, may negatively affect deacetylase expression/activity, thus, supporting increased pro‐inflammatory responses.The findings here provided suggest a new role of combination therapy with carbocysteine and beclomethasone dipropionate in restoring deacetylation processes compromised by cigarette smoke exposure.